Case report: Treatment of severe phorate poisoning - Kunlun, Wang; Jun, Yuan; Shiming, Xu; Jie, Shen; Mingqiang, Gao; Yuxia, Zhang; Weichun, Mo (Frontiers in Toxicology, 2025)
BackgroundPhorate is a highly toxic organophosphorus pesticide. Owing to its low cost and insecticidal potency, it is still widely used in parts of China, resulting in cases of occupational and life poisoning. This article presents the treatment process for phorate poisoning and monitoring the toxic metabolites terminology in the body.Case reportA 23-year-old male patient ingested about 300 mL (180 g) of 60% phorate emulsion 4 h before admission at our hospital. The patient had ingested over 300 times the lethal dose. During hospitalization, the patient’s levels of cholinesterase, phorate and its metabolites, atropine and pralidoxime chloride (PAM), were monitored. Phorate was quickly absorbed into the blood, producing five metabolites. Before hemoperfusion (HP), the concentration of phorate in the blood could not be detected. After the first HP we found five metabolites of phorate in the blood (phoratoxon sulfoxide,phoratoxon sulfone, phorate sulfone, phorate sulfoxide, and phoratoxon). In the follow-up treatment, the concentration of five metabolites gradually decreased. The concentration of the phorate sulfoxide and phorate sulfone rebounded with the suspension of HP, but that of the other metabolites did not rebound. It took 20 days for cholinesterase to recover. Treatment included multiple rounds of HP, atropinization, and reactivator of cholinesterase by PAM. The patient recovered after 34 days and was discharged from hospital.ConclusionPhorate is oxidized and catalyzed into five metabolites, which cause the toxic effects. Phoratoxon sulfoxide has the highest concentration of these metabolites, followed by phoratoxon sulfone, phorate sulfone, phorate sulfoxide, and phoratoxon, respectively. HP treatment significantly lowered the serum levels of the toxic metabolites terminology. If HP treatment is interrupted, the serum levels of phorate sulfoxide and phorate sulfone tend to rise again. It takes a long time for cholinesterase to recover from severe phorate poisoning.